2004
DOI: 10.1002/dev.20019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of object spatial location and task complexity on children's use of their preferred hand depending on their handedness consistency

Abstract: The goal of the present study was to compare the use of the preferred versus the nonpreferred hand in children performing two tasks of different levels of complexity, in various positions in space. Right-handed and left-handed consistent children were compared to their inconsistent counterparts. The results showed that the general tendency to use one's preferred hand to grasp an object is more or less pronounced depending on the object's spatial location and the task's complexity. The children used their prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 52 publications
7
46
0
2
Order By: Relevance
“…Since some studies have shown a relationship between handedness and asymmetry in the adult brain (Rademacher et al, 2001;Hervé et al, 2009) while other studies have shown no such relationship (Westerhausen et al, 2007;Ciccarelli et al, 2003;Reich et al, 2006), we cannot exclude the possibility that right side preference for spontaneous movements may be related to an asymmetrical position within the womb that frees the right side (Hepper et al, 1991), and/or environmental factors that would favour one side (Leconte and Fagard, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Since some studies have shown a relationship between handedness and asymmetry in the adult brain (Rademacher et al, 2001;Hervé et al, 2009) while other studies have shown no such relationship (Westerhausen et al, 2007;Ciccarelli et al, 2003;Reich et al, 2006), we cannot exclude the possibility that right side preference for spontaneous movements may be related to an asymmetrical position within the womb that frees the right side (Hepper et al, 1991), and/or environmental factors that would favour one side (Leconte and Fagard, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…If the larger part of the children were right-handers, which is in accordance with the day-care employees' verbal reports, the higher dexterity of the right hand enabled them to organize a more difficult and less comfortable (i.e., involving more degrees of freedom) movement like pulling. This indicates that biomechanical factors, in addition to the task-related factors, are an inherent part of the task performance (see e.g., LeConte & Fagard, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In other words, when the children shifted to the ipsilateral non-preferred eye, was it because they first grasped the telescope with the ipsilateral hand? There is a known tendency to use the ipsilateral hand to point to or to grasp laterally presented targets (Leconte & Fagard, 2004). To evaluate whether or not eye choice for sighting reflected hand choice for grasping, we first looked at the relationship between eye and hand used when the target was presented in the center, for both stimuli.…”
Section: Degree Of Eye Preference (Varying Angle Of Sighting)mentioning
confidence: 99%
“…Most of the eye preference results were obtained with the eyes pointed straight ahead. As it is the case for the non-preferred hand, frequently used when the object to be grasped is on the same side (Leconte & Fagard, 2004), the eye chosen for sighting is influenced by spatial factors: if the target to be looked at is on the side of the nonpreferred eye, then individuals tend to use the ipsilateral eye more than the preferred one (Khan & Crawford, 2001).…”
Section: Introductionmentioning
confidence: 99%